THE APPLICATION OF SOCIAL SKILL TRAINING AS INTERVENTION TO IMPROVE SOCIAL SKILL FOR A SMALL NUMBER OF FRESHMEN STUDENTS - Witarso, Laurentius Sandi; Utoyo, Dhamayanti B. (International Journal of Indonesian Education and Teaching (IJIET), 2018)
Being freshmen is a challenge for college students. They must encounter a lot of demands in their college especially their social skills. Prior research showed that students of Universitas Indonesia reported their social-psychological relations problem in their social environment. Freshmen must have adequate social skills in order to encounter demands in social relation. This study aimed to increase social skills for Universitas Indonesia’s freshmen through the application of Social Skill Training (SST). A pre-test, post-test design and one month follow up test were administered. Subjects of this study were seven Universitas Indonesia’s students (freshmen) with age range from 17 – 18 years old, attended three sessions with two hours per session. Participants reported that their social skills increased, indicated by improvement in Social Skills Inventory (SSI), and also by qualitative evaluation. Group dynamics and experiential learning allowed them to learn from the experiences of other participants. Therefore, the application of Social Skills Training effectively increased the social skills for Universitas Indonesia’s freshmen. Further research is needed to examine this intervention using a larger sample, control groups and in-depth interview for qualitative evaluation. DOI: https://doi.org/10.24071/ijiet.2018.020204